Male post-prostatectomy incontinence MDT. (November 2017) - Fairbanks, Jessica; Duffy, Megan; Hamid, Rizwan; Ockrim, Jeremy; Greenwell, Tamsin J
The management of post-prostatectomy incontinence remains controversial with ongoing confusion as to who benefits from male sling or artificial urinary sphincter. We present a post-prostatectomy incontinence MDT format to illustrate key factors in decision-making and determination of best management in post-prostatectomy incontinence.